Anatomia da madeira e dendrocronologia de Pterodon emarginatus Vogel (Fabaceae) na Serra do Cipó, MG-Brasil - Aryane Évelyn Barbosa Nunes (2019)
The sensitivity of vascular cambium to seasonal changes and genetic factors promotes the formation of growth rings in many woody plants. In the “Serra de Cipó-MG” National Park, seasons well marked by periods of rain and drought occur with rainfall below 60 mm in the driest months. Pterodon emarginatus is found in gallery forests and seasonal forests, and water availability in relation to different micro-habitats and macroclimate can be factors that cause intraspecific variations in the wood of this species and annual growth records. Current objective was to analyze the wood the native species Pterodon emarginatus Vogel from anatomical and cross-dating perspectives with the purpose of evaluating its dendrochronological potential, since this plant species has rings marked by marginal parenchyma associated to fibrous zones. Individuals (n = 5 per locality) were selected near the “Ribeirão Farofa”, considered the location with permanent water source, and individuals near “Mirante do Bem”, region where there is no permanent watercourse. Quantitative and qualitative characteristics were analyzed according to the IAWA Committee. Histological sections and dissociation of wood samples were processed, measured and analyzed. Physical and chemical soil analyzes were also carried out. For the dendrochronological potential, wood discs (n = 5) were collected, polished and submitted to counting and measurements of their rings. COFECHA software was used to assess the quality of cross-dating and measurement accuracy of tree -ring series. The resulting values of the ring width were transformed into growth index by the ARSTAN software generating a single master series from 1795 to 2017 and compared with climatic data from “Estação Meteorológica de Diamantina” – “Instituto Nacional de Meteorologia” (INMET). No significant differences were found between the quantitative characteristics. There were similarities in qualitative and soil analyzes between two evaluated areas, with higher amounts of minerals K, Mg2+, B, Fe and Mn found in “Mirante do Bem” area in relation to “Ribeirão Farofa”. This increase can be explained by the flow of rainwater from higher adjacent regions to the flatter region where P. emarginatus individuals are located. Although the soil in “Mirante do Bem” has proportions below 35% clay and above 45% sand, it can be enflamed as sandy and classified as having medium texture due to the equivalent proportions of sand, silt and clay. These data indicate that, in addition to being well adapted, individuals have a common anatomical pattern. Four of the analyzed discs had a better correlation with the master series (0.395), high values of mean sensitivity (0.396) and standard deviation (0.437). These values were satisfactory due to the and/or semideciduous species with strong indications of being annual. It was not possible to confirm the influence of precipitation on the formation of growth rings, due to the limited number of collections, and legal implications of collecting in a national park. Current results indicated that P. emarginatus can be a model species for climate-growth relationships due to presence annual rings. (CAPES, PPGBV-UFMG, ICMBio).